1993
DOI: 10.1002/cber.19931260820
|View full text |Cite
|
Sign up to set email alerts
|

[α‐(Dimethylamino)benzyllithium–Diethyl Ether]2, (S)‐α‐(Methylpivaloylamino)benzyllithium – (–)‐Sparteine, and [3‐Iodo‐2‐lithio‐1‐methylindole – 2 Tetrahydrofuran]2: Crystal Structure Investigations of α‐Lithiated Amines

Abstract: In order to determine whether a-metalated (lithiated) amines are carbenoids, as are a-lithiated halides and ethers, we have determined the crystal structures of the title compounds. In does not bridge to the indole nitrogen atom because it is a weak donor. The C-N bond length to the anionic C atom is slightly longer (2 -3 pm) than in the non-lithiated compound. Other a-lithiated amines, which have been published, although not analyzed so far under this particular aspect, show also a marginal C-N bond lengtheni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(42 citation statements)
references
References 81 publications
3
37
0
2
Order By: Relevance
“…This bridged motif has also been observed in additional α ‐lithio amines by means of NMR spectroscopy 11. Such a structure might represent the first step in a “conducted tour” process for an α ‐hetero organolithium compound which proceeds via the ion pair 7 (Scheme ) 12…”
Section: Spectroscopic and Chemical Methods For Determining Configmentioning
confidence: 60%
“…This bridged motif has also been observed in additional α ‐lithio amines by means of NMR spectroscopy 11. Such a structure might represent the first step in a “conducted tour” process for an α ‐hetero organolithium compound which proceeds via the ion pair 7 (Scheme ) 12…”
Section: Spectroscopic and Chemical Methods For Determining Configmentioning
confidence: 60%
“…[39] The crystal structure of the a-lithiated benzyl amide 23 shows both intramolecular and intermolecular ligand binding. [40] Studies of ground-state structures also show agostic interactions between CÀH bonds and lithium atoms, which may precede proton transfer and can be interpreted to provide support for CIPE. A survey of X-ray crystal structures supports a systematic weakening of CÀH bonds associated with lithium atoms.…”
Section: Methodsmentioning
confidence: 95%
“…Selected bond distances (inÅ) at the α-C atom of some 1,2-diamino-1,2-diphenylethane derivatives from single crystal XRD experiments a . by results of Reich et al, who reported that spinspin coupling of 6 Li to 13 C and 15 N in a solution of 2-[(dimethylamino)methyl]phenyllithium in THF disappears at temperatures above −55 • C [5]. Since dissociation and charge separation are likely to increase the entropy of the system, it can be rationalized why formation of 2 is favored at higher temperatures in this solvent.…”
Section: 2-diphenylethanementioning
confidence: 94%
“…Reich and co-workers investigated the solution structure of the o-lithiated N, N-dimethylbenzylamine and found several dimers to coexist at temperatures below −55 • C [5]. Boche et al succeeded in isolating the diethylether adduct of α-lithiated 0932-0776 / 05 / 1000-1083 $ 06.00 c 2005 Verlag der Zeitschrift für Naturforschung, Tübingen · http://znaturforsch.com N, N-dimethylbenzylamine from the reaction of tri-nbutyl[α-(dimethylamino)benzyl]stannane with n-BuLi in hexane at 0 • C, and to investigate its molecular structure in the solid state [6].…”
Section: Introductionmentioning
confidence: 99%